Efektivitas Integrasi Muatan Lokal Pendidikan Diniyah Dalam Peningkatan Kemampuan Pendidikan Agama Islam Siswa: Studi Kasus di SMPN 5 Jombang - Nuning Etikoh; Zahrotun Ni’mah Afif (LP3M IAI Al Urwatul Wutsqo Jombang, 2023)
This study aims to describe the local content of madrasa education implemented at SMPN 5 Jombang and analyze its implications for improving students' Islamic Education (PAI) skills. This qualitative research with a case study design involves the principal, teachers, and 60 students from grades 4-6 as subjects. Data collection is done through observation, interviews, documentation studies, and questionnaires. The results showed that SMPN 5 Jombang had integrated five madrasa subjects as local content in its curriculum. Management of local content looks mature and structured. The impact on improving PAI skills of students is very positive, as indicated by an increase in the average value of PAI, improved religious behavior and discipline of student worship. However, several obstacles were also found such as limited learning hours and the methodological competence of teachers that needed to be improved. With proper mitigation, the integration of madrasa local content has the potential to improve the quality of learning and PAI skills of elementary school students, as long as the planning and management are carried out in a structured and systematic manner